A retrospective, multi-center analysis of treatment intensification for human immunodeficiency virus-positive patients with high-risk diffuse large B-cell lymphoma. Issue 9 (September 2013) - Kassam, Shireen; Bower, Mark; Lee, Siow Ming; de Vos, Johannes; Fields, Paul; Gandhi, Shreyans; Nelson, Mark; Montoto, Silvia; Tenant-Flowers, Melinda; Burns, Fiona; Marcus, Robert; Edwards, Simon G.; et al.
Abstract: This analysis reviews the response rate (RR), treatment toxicity and overall survival (OS) for human immunodeficiency virus (HIV)-positive patients with high-risk diffuse large B-cell lymphoma (DLBCL) and the impact of treatment intensification. Fifty patients, treated with either rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone (R-CHOP) ( n = 35) or cyclophosphamide, vincristine, doxorubicin, methotrexate/etoposide, ifosfamide, cytarabine (CODOX-M/IVAC) ± R ( n = 15) chemotherapy, were included. Baseline characteristics did not differ between the two treatment groups. Forty-seven patients (94%) received rituximab and 48 (96%) received combination anti-retroviral therapy, with chemotherapy. The RR and treatment-related mortality were not significantly different between the two groups. Overall, 68% achieved complete remission. There were significantly more infections and non-hematological toxicities in the CODOX-M/IVAC ± R group. With a median follow-up of 28 months, 2-year progression-free survival (PFS) and OS are 68% and 70%, respectively, with no significant differences in remission duration, PFS or OS between the groups. In our cohort, the outcome for HIV-positive patients with high-risk DLBCL is favorable. Treatment intensification is feasible, but demonstrated no advantage over R-CHOP.